Bitter root. Volume two, Rage & redemption - Walker, David, 1968-; Brown, Chuck (Comic book author) (Image Comics, Inc., 2020)
"Monster-hunting has been the Sangerye family business for generations as they battle the jinoo--hideous creatures born out of hate and racism. But now the Sangeryes face a different threat--the deadly inzondo, a new kind of monster born out of grief and trauma. With one of their own turning into an inzondo and an army of tortured souls on the attack in 1920s Harlem, the Sangerye family must once again fight to save the world, unless their own pain and suffering transforms them into monsters as well!"--